Sistem Informasi Pelaporan Penggunaan Alsintan Pada Kelompok Tani di Kabupaten Jombang Berbasis Android - Tholib Hariono; Hellyou Susanti (JOURNAL SAINS STUDENT RESEARCH, 2025)
Digital transformation in the agricultural sector has become a strategic necessity to improve the efficiency and accuracy of managing agricultural machinery and equipment (alsintan). Jombang Regency, as an agrarian region, has implemented a web-based reporting system (SIMANTAN), yet still faces challenges such as limited accessibility, low digital literacy, and slow reporting processes. This study aims to design and develop an Android-based alsintan usage reporting information system to enable farmer groups to submit reports more easily, quickly, and accurately. The development method uses the Waterfall approach, consisting of requirements analysis, design, implementation, testing, and maintenance. The resulting application allows real-time reporting and the uploading of photographic evidence of equipment usage. Testing results indicate that the system operates according to user requirements, enhancing effectiveness and transparency in the use of alsintan at the farmer group level. This system is expected to serve as a digital solution contributing to the equitable distribution and fulfillment of alsintan needs in Jombang Regency.